Physique and body composition in soccer players across adolescence - Nikolaidis, P. T.; Karydis, N. V. (Asian Journal of Sports Medicine, 2011)
Although the contribution of physique and body composition in soccer performance was recognized, these parameters of physical fitness were not well-studied in adolescent players. Aim of this study was to investigate physique and body composition across adolescence.